2002 IEEE Wireless Communications and Networking Conference Record. WCNC 2002 (Cat. No.02TH8609)
DOI: 10.1109/wcnc.2002.993531
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale testbed for reproducible ad hoc protocol evaluations

Abstract: We have built an Ad hoc Protocol Evaluation testbed (APE) in order to perform large-scale, reproducible experiments. APE aims at assessing several different routing protocols in a real world environment instead of by simulation. We present the APE testbed architecture and report on initial experiments with up to 37 physical nodes that show the reproducibility and scalability of our approach. Several scenario scripts have been written that include strict choreographic instructions to the testers who walk around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 8 publications
0
71
0
Order By: Relevance
“…The first and main reason is the lack of quality real world implementations. When we started building the Ad hoc Protocol Evaluation Testbed in the year 2000 [9], we had a hard time finding (a) any implementations, and (b) implementations that worked properly. Out of three protocol implementations (OLSR, AODV, TORA), only one was able to route packets over multiple hops.…”
Section: Methodsmentioning
confidence: 99%
“…The first and main reason is the lack of quality real world implementations. When we started building the Ad hoc Protocol Evaluation Testbed in the year 2000 [9], we had a hard time finding (a) any implementations, and (b) implementations that worked properly. Out of three protocol implementations (OLSR, AODV, TORA), only one was able to route packets over multiple hops.…”
Section: Methodsmentioning
confidence: 99%
“…In the experiments, it is found that the CrossROAD over OLSR outperforms traditional P2P systems over AODV. Some 9 to 37 nodes are used within four mobility groups indoor on AODV and OLSR protocols, and it is found that the approach of choreographing node movement is suitable for real-life MANET testing [19] . An investigation has been carried out on the throughput of the IEEE 802.11 distributed coordination function considering a number of factors, e.g., path loss, multi-path fading [20] .…”
Section: Background and Related Workmentioning
confidence: 99%
“…The goal of these tools is to give researchers the same flexibility and usability during implementation-based experiments as provided by a typical network simulation tool. APE [22] and MTM [23] are examples of this class.…”
Section: A Software Toolsmentioning
confidence: 99%